Pesticidas, saúde e ambiente e os tabus dos pesticidas em Portugal - Amaro, Pedro (2008)
During the last 17 years was intensified, by the Nacional Pesticides Authority and the pesticides industry, the pesticide designation tabu and the tabu concerning, the hazard classification of pesticides with specific effects on human health and the risk phrases.The warning about the inconvenients of the last tabu concerning the high probability of occurrence of unacceptable risk to human health was insufficient to obtain any results.